Quality control on the frontier - Paszkiewicz, Konrad H.; Farbos, Audrey; O'Neill, Paul; Moore, Karen (Frontiers in Genetics, 2014)
In the world of high-throughput sequencing there are numerous challenges to effective data quality control. There are no single quality metrics which are appropriate in all conditions. Here we detail the different open source software used at the Exeter Sequencing Service to provide generic quality control information, as well as more specific metrics for genomic and transcriptomic libraries run on Illumina platforms.